Plasma Fibroblast Growth Factor 21 Is Associated With Severity of Nonalcoholic Steatohepatitis in Patients With Obesity and Type 2 Diabetes - Barb, Diana (J Clin Endocrinol Metab, 2019)
CONTEXT: The relationship between plasma fibroblast growth factor 21 (FGF21), insulin resistance, and steatohepatitis has not been systematically assessed. OBJECTIVE: To determine if higher plasma FGF21 is associated with worse steatohepatitis on liver biopsy in patients with nonalcoholic fatty liver disease (NAFLD). DESIGN AND SETTING: Cross-sectional study in a university hospital. PATIENTS INTERVENTIONS AND MAIN OUTCOME MEASURES: Patients with a body mass index >25 (n = 187) underwent: (i) euglycemic hyperinsulinemic clamp to assess tissue-specific insulin resistance (IR); (ii) liver magnetic resonance spectroscopy for intrahepatic triglyceride quantification, (iii) liver biopsy (if NAFLD present; n = 146); and (iv) fasting plasma FGF21 levels. METHODS AND RESULTS: Patients were divided into three groups: (i) No NAFLD (n = 41); (ii) No nonalcoholic steatohepatitis (NASH) (patients with isolated steatosis or borderline NASH; n = 52); and (iii) NASH (patients with definite NASH; n = 94). Groups were well-matched for age/sex, prevalence of type 2 diabetes mellitus, and hemoglobin A(1c). During euglycemic hyperinsulinemic insulin clamp, insulin sensitivity in skeletal muscle and adipose tissue worsened from No NAFLD to NASH (both P < 0.001). Plasma FGF21 levels correlated inversely with insulin sensitivity in adipose tissue (r = −0.17, P = 0.006) and skeletal muscle (r = −0.23, P = 0.007), but not with liver insulin sensitivity. Plasma FGF21 was higher in patients with NASH (453 ± 262 pg/mL) when compared with the No NASH (341 ± 198 pg/mL, P = 0.03) or No NAFLD (325 ± 289 pg/mL, P = 0.02) groups. Plasma FGF21 increased with the severity of necroinflammation (P = 0.02), and most significantly with worse fibrosis (P < 0.001), but not with worsening steatosis (P = 0.60). CONCLUSIONS: Plasma FGF21 correlates with severity of steatohepatitis, in particular of fibrosis, in patients with NASH. Measurement of FGF21 may help identify patients at the highest risk of disease progression.